The characteristics of horse bones from the late roman period - Mihelić, Damir (Array, 2008)
During an archaeological excavation at the site of the School of Agriculture, Osijek, well preserved horse bones and bone particles from late Roman period were found. Our research showed that these bone-remains are stronger compared to contemporary sport breeds, indicating a higher resemblance with present-day autochthonous horse breed.